2023
DOI: 10.1111/ppl.13939
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors TgbHLH42‐1 and TgbHLH42‐2 positively regulate anthocyanin biosynthesis in Tulip (Tulipa gesneriana L.)

Abstract: The floral coloration of tulip flowers is one of the most prominent traits contributing to its high ornamental value. The molecular mechanisms of petal coloration remain elusive in tulip species. In this study, we performed comparative metabolome and transcriptome analyses using four tulip cultivars with distinguished petal colors. Four types of anthocyanins were identified, including cyanidin derivatives and pelargonidin derivatives. Comparative transcriptome analysis identified 22,303 differential expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…TgMYB4 contains a bHLH-interacting motif ( Figure 1 B), which was identified as a conserved domain of subgroup 4 R2R3-MYBs and was shown to interact with the bHLH component of the MBW complex. TgbHLH42-1 plays a positive role in the regulation of anthocyanin in tulips, and has a high homology to AtTT8 [ 44 ]. In order to dissect the working mechanism of TgMYB4 , we explored the relationship between TgMYB4 and TgbHLH42-1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…TgMYB4 contains a bHLH-interacting motif ( Figure 1 B), which was identified as a conserved domain of subgroup 4 R2R3-MYBs and was shown to interact with the bHLH component of the MBW complex. TgbHLH42-1 plays a positive role in the regulation of anthocyanin in tulips, and has a high homology to AtTT8 [ 44 ]. In order to dissect the working mechanism of TgMYB4 , we explored the relationship between TgMYB4 and TgbHLH42-1.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that the AtPAP1-TgbHLH42-1 complex could activate the transcription of AtDFR through dual luciferase assays [ 44 ]. In this study, we investigated whether TgMYB4 could attenuate the ability of the MYB-bHLH complex to activate AtDFR .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations